CREATION OF GOOGLE SITES-BASED E-MODULES FOR DIGITAL DOCUMENT ELEMENTS AT HIGH VOCATIONAL SCHOOLS - Febriani, Ellizah; Zulaihati, Sri; Adha, Maulana Amirul (Faculty of Economics and Business, Universitas Negeri Jakarta, 2024)
This research aims to evaluate the feasibility and practicality of developing an e-module based on Google Sites for digital document elements. The study was conducted at SMK Negeri 40 Jakarta in class X Office Management with 36 participating students. The method used is Research and Development (R&D) with the ADDIE development model (Analyze, Design, Development, Implementation, and Evaluation). The research subjects consisted of 9 validators (three subject matter experts, three instructional design experts, and three media experts) and 36 class X MP students. The data analysis techniques included validation tests and practicality tests. The validation test was conducted by subject matter experts with a result of 88%, categorized as highly feasible; instructional design experts with a result of 97%, categorized as highly feasible; and media experts with a result of 90%, categorized as feasible. The practicality test was conducted by 36 class X MP students through three stages of trials: one-to-one evaluation with a result of 93%, considered highly practical; small group trials with a result of 92%, considered highly practical; and large group trials with a result of 91%, considered highly practical. The results of the research and development indicate that the e-module based on Google Sites for digital document elements at SMK Negeri 40 Jakarta is deemed highly feasible and highly practical for use in learning activities.